Nursing interventions in the prevention of postpartum hemorrhage: A systematic review - Jenoveva Soares; Nopi Nur Khasanah; Sri Wahyuni (School of Health Sciences Al-Ma'arif, 2026)
Background: Postpartum hemorrhage (PPH) remains a major cause of preventable maternal morbidity and mortality. Nursing and midwifery interventions may contribute to risk recognition, early response, clinical monitoring, and professional preparedness; however, the available evidence is methodologically diverse. Objective: To synthesize eight eligible publications on nursing and midwifery contributions to postpartum hemorrhage (PPH) prevention and early management, including primary intervention evidence and contextual or conceptual evidence, and to examine their relevance to Wiedenbach's Need for Help theory. Methods: This systematic review was reported in accordance with PRISMA 2020. PubMed, ProQuest, SAGE Journals, and ClinicalKey for Nursing were searched for English-language publications from January 2015 to December 2025. The search identified 5,397 records, 56 full-text reports were assessed, and eight publications were included: four primary intervention studies and four contextual or conceptual publications. Design-appropriate Joanna Briggs Institute appraisal criteria were used, and findings were synthesized narratively in separate evidence strata. Results: The eight included publications comprised one randomized clinical trial, one non-randomized controlled study, two one-group pretest-posttest studies, one qualitative evidence synthesis, one integrative review, one narrative review, and one conceptual paper. Primary clinical studies reported reductions in blood-loss scores or nursing risk events, while educational studies reported improved knowledge or competency. Contextual sources highlighted physiological care strategies, objective monitoring, communication, resource readiness, and barriers to timely recognition. None of the publications directly tested Wiedenbach's theory. Conclusion: Nursing and midwifery interventions show potential to strengthen PPH prevention and early management.